Impact of ultraviolet radiation on filtering facepiece respirators and SARS-CoV-2 detection - Khaled Al-Hadyan; Najla Al-Harbi; Sara Bin Judia; Maha Al-Ghamdi; Ibtihaj Alsharif; Layla Alharbi; Maha Al-Mozaini; Belal Moftah; Belal Moftah; Salem Al-Ghamdi; Ghazi Alsbeih; Ghazi Alsbeih (Frontiers in Public Health)
IntroductionThe global coronavirus disease (COVID-19) pandemic of 2020 caused by SARS-CoV-2 resulted in a shortage of filtering facepiece respirators (FFRs), such as N95 and KN95 masks. Ultraviolet-C (UV-C) irradiation has been proposed as a potential decontamination method to enable FFR reuse and mitigate the shortage. This study aims to evaluate the impact of UV-C irradiation on the filtration efficiency (FE) of various FFR types and SARS-CoV-2 RNA degradation.MethodWe evaluated the effect of UV-C irradiation (60–900 mJ/cm2) on the FE using various particle sizes (PSs, 0.3–5 μm) representing seven common FFR types (3M-8210, 3M-1860, Gerson 1730, Medline, Benehal, KN95 “duck shape,” and KN95 “molded shape”) and the stability of the SARS-CoV-2 RNA genes (E, RdRp2, RdRp4, and N) using reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR).ResultsFollowing UV-C exposure, the FE of the FFRs at all PSs was >98%, with no significant differences among them (p > 0.05). UV-C irradiation significantly increased the RT-qPCR cycle threshold values (ΔCt) for the E, RdRp2, and RdRp4 SARS-CoV-2 genes (p ≤ 0.001) compared with the control, indicating marked RNA degradation; however, it did not significantly affect N gene stability (p = 0.612).DiscussionThese results support the use of UV-C as an effective decontamination technique for FFRs, particularly during periods of shortage.